Uptake of public health measures and vaccine acceptance during the COVID-19 pandemic in rural Zambia - Catherine G. Sutcliffe; Pamela Sinywimaanzi; Juliet Morales; Morris Sianyanda; Mathias Muleka; Katherine Z. J. Fenstermacher; Mwaka Monze; Richard E. Rothman; Andrew Pekosz; Philip E. Thuma; Edgar Simulundu (Human Vaccines & Immunotherapeutics, 2022)
Vaccines are effective tools to prevent COVID-19-related morbidity. However, coverage is low throughout sub-Saharan Africa. Uptake of public health measures, perceptions of COVID-19 illness and vaccines, and intention to vaccinate were evaluated in 2021–2022 in rural Zambia. Adherence to public health measures, perceptions of COVID-19 risk and severity, and vaccine acceptance increased significantly over time, particularly in December 2021, coinciding with the fourth pandemic wave and relaunch of the national vaccine campaign. Vaccine acceptance was associated with perceptions of vaccine safety and effectiveness, but not disease severity. These findings highlight the importance of strong pandemic response and public communication for increased uptake of mitigatory measures, including vaccine acceptance.